Effect of Guava Leaves Powder on the Oxidative and Microbial Stability of Chicken Meat Nuggets during Refrigerated (4±1°C) Storage - Kola, Manjula; Reddy G V, Bhaskar; Bandi, Kalyani; Donadi, Jhansi (Journal of Meat Science, 2026)
The present study was carried out to evaluate the efficacy of different levels (0.5  and 1 per cent) of guava leaf powder (GLP) (Psidium guajava L) with synthetic  antioxidant ie) butylated hydroxy toluene (BHT) at 0.01 % was studied on  physico-chemical, microbial and sensory quality characteristics of chicken  meat nuggets under aerobic packaging conditions during refrigerated storage  (4±1°C). The chicken nuggets added with 1 % GLP had significantly (P < 0.05)  lower 2-thiobarbituric acid reactive substance (TBARS) values and free fatty  acid (FFA) content compared to control nuggets and other samples during  refrigerated storage (4±1°C). A significant (P
Keywords: Guava leaf powder; antioxidants; antimicrobial agents; chicken meat nuggets; storage stability.